1991
DOI: 10.1002/crat.2170260105
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Single Crystals of the Ternary Compound TlGaTe2

Abstract: Growth and Characterization of Single Crystals of the Ternary Compound TIGaTe,The electrical conductivity and the Hall effect for TlGaTe, crystals have been measured over a wide temperature range. The crystal used for our study was grown by the Bridgman technique and possessed p-type conductivity. The energy gap has been found to be 0.84 eV, whereas the ionization energy has the value 0.25 eV. The variation of the Hall mobility as well as the carrier concentration with temperature was investigated. The scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
2
9
3
Order By: Relevance
“…The value of the conductivity, being of the order of ∼10 −3 Ω cm −1 is lower than that reported for the same crystals, ∼3.33 × 10 −2 Ω cm −1 , in Ref. 1. The difference in the conductivity values may be attributed to the crystal defects and/or atomic vacancies that may have occurred during the crystal growth process.…”
Section: Resultscontrasting
confidence: 61%
See 2 more Smart Citations
“…The value of the conductivity, being of the order of ∼10 −3 Ω cm −1 is lower than that reported for the same crystals, ∼3.33 × 10 −2 Ω cm −1 , in Ref. 1. The difference in the conductivity values may be attributed to the crystal defects and/or atomic vacancies that may have occurred during the crystal growth process.…”
Section: Resultscontrasting
confidence: 61%
“…The value of the bandgap for TlGaTe 2 crystal was reported as 0.82 eV 1, 6. Our Hall effect data analysis (not presented here) has shown that the energy level at 0.26 eV obtained from the dark electrical conductivity analysis is an acceptor level.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…1b, reected no change in the resistivity activation energy (0.2 eV) along the a-axis, it exhibits a pronounced change from 0.26 to 0.41 eV above 330 K along the c-axis. The value of resistivity activation energy being 0.41 eV coincides with E g /2 (middle of energy band gap) and results in an energy band gap of 0.82 eV indicating that the crystal convert from extrinsic to intrinsic type semiconductor along the c-axis at temperature of 330 K. The energy band gap of TlGaTe 2 being 0.82 eV is close to that determined from band structure analysis as 0.86 eV [13] and as 0.84 eV [14]. Figure 2 displays the temperature dependence of the current densityvoltage characteristics being recorded along the a-axis.…”
Section: Resultssupporting
confidence: 73%
“…10 The abnormal behavior of mobility was attributed to high density of stoichiometric vacancies and creation of defects in the crystal. 17,18 B. Temperature-dependent steady state photoconductivity TlGaSeS single crystals are observed to exhibit room temperature light photosensitivity (S ¼ (I light À I dark )/I dark ) of 3.85 at 76.7 mW cm À2 . Figure 3 reflects the variation of steady state photocurrent (I ph ) as a function of reciprocal temperature being recorded at different light intensities in the range of 27.9-76.7 mW cm À2 .…”
Section: Methodsmentioning
confidence: 99%